2016
DOI: 10.3390/rs8090776
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Fractional Vegetation Coverage and Its Relationship with Climate and Human Activities in Inner Mongolia, China

Abstract: Long-term remote sensing normalized difference vegetation index (NDVI) datasets have been widely used in monitoring vegetation changes. In this study, the NASA Global Inventory Modeling and Mapping Studies (GIMMS) NDVI3g dataset was used as the data source, and the dimidiate pixel model, intensity analysis, and residual analysis were used to analyze the changes of vegetation coverage in Inner Mongolia-from 1982 to 2010-and their relationships with climate and human activities. This study also explored vegetati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 21 publications
3
22
0
Order By: Relevance
“…The Pearson's correlation coefficient was 0.773 (p < 0.01, RMSE = 0.091), which meets the accuracy requirements ( Figure 5), indicating that the DPM was reliable in extracting the FVC. This is also consistent with previous findings [3].…”
Section: Fvc Growth Ratesupporting
confidence: 83%
See 2 more Smart Citations
“…The Pearson's correlation coefficient was 0.773 (p < 0.01, RMSE = 0.091), which meets the accuracy requirements ( Figure 5), indicating that the DPM was reliable in extracting the FVC. This is also consistent with previous findings [3].…”
Section: Fvc Growth Ratesupporting
confidence: 83%
“…It confirmed that China has been undergoing significant large-scale policy-driven ecological restoration [26]. However, the effects on a large scale do not necessarily occur on a small scale, and previous studies have concluded the relationship between vegetation transitions and natural or human-induced factors at a global, national, or regional level; the provincial and/or city scale is lacking [3,27,28]. Furthermore, there are also very few investigations of the spatial heterogeneity of human activity's influential effects.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…It is a water conservation area of Songhua River and functions as an important ecological barrier of northern China [11,12]. The ecological environment in IMAR is characterized by distinctive geographical differences, fragile ecological conditions, and complex ecological types [12][13][14], where vegetation types show a northeast-southwest pattern of surface cover of forests, steppes and deserts [12,15]. Quantitative assessment of the dynamic changes and driving forces of the vegetation ecosystem in Inner Mongolia will help people to understand the feedback between the global climate change and vegetation ecosystems [12,[14][15][16], which is of great theoretical and practical significance for evaluating the environmental quality of terrestrial ecosystems and regulating ecological processes [1,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the FVC was retrieved from a sub-pixel model, which assumes the remotely sensed response in a mixed pixel is composed of a linearly weighted combination of vegetated and non-vegetated components, with the most widely used remote sensing spectral response being NDVI [43], since NDVI is the optimal indicator of vegetation growth and strongly correlated with vegetation cover [44]. The calculation formula of the sub-pixel model is calculated as [45]:…”
Section: Fractional Vegetation Cover Calculationmentioning
confidence: 99%